LONG TERM EVALUATION OF RADIOGRAPHICALLY UNDETECTED ACUTE OSTEOMYELITIS RESULTING CHRONIC OSTEOMYELITIS WITH MRSA - Taufan Adityawardhana; Sulis Bayusentono (Jurnal Ilmu Kesehatan dan Kesehatan, 2020)
Osteomyelitis is an infection and inflammation of the bone that can spread into all parts of the bone. Methicillin-resistant Staphylococcus aureus or MRSA made the disease’s management far more complex and constrained and 28% of hospitals in Indonesia are suspected to be MRSA endemic. Osteomyelitis combined with MRSA have obscured prognosis knowing its assessment and management are still being developed. Presenting a case of Chronic Osteomyelitis and MRSA of 11-year old girl that has been monitored for 5 years after the reported onset since July 2015. The patient complained of severe pain in the left hip region causing her to stop using her left limb in July 2015. Signs of acute osteomyelitis couldn’t be confirmed by sequential assessments of X-Ray and USG examination. Cefazolin and Gentamicin injections were administered for 23 days. The family requested the patient to be sent home, due to no significant clinical improvement as indicated by them. Antibiotic regimens changed into oral regimens, which were Co-Amoxiclav and Gentamicin. The patient never appeared for routine check-up, her family conceded that they went to traditional alternative medication and stated the patient's clinical outcomes were showing signs of improvement; where the patient was able to walk normally. 6 months after, the patient's mother observed abnormal gait, however the patient didn't mention nor complain anything. X-ray assessment was then performed, with the result of the entire left femoral head being reportedly destroyed. In January 2016 the patient was referred to dr. Soetomo Academic General Hospital, the patient was diagnosed with chronic osteomyelitis and pathological fracture of 1/3 proximal left femur with a suspicion of avascular necrosis. The patient was given prophylactics antibiotics. Closed biopsy couldn't be performed hence open biopsy was suggested. The patient had routine check-ups to monitor the disease progression, alongside radiologic assessment and laboratory assessment prior to the operation. Episodes of localised swollen and tenderness in the hip area were accounted. Scenes of seropurulent discharges were additionally reported. In june 2017 patients had surgical debridement and sequestrectomy alongside an open biopsy, where MRSA was diagnosed. No antibiotics had been given after the surgery and the patient routinely washed up with Chlorhexidine Gluconate 4%. The patient still does routine check-ups at the outpatient facility, as radiologic and laboratory examination are routinely observed. As of now, the patient has no issue in its daily living activities. There is still limited range of movement at the infected site, with 90 degree of hip flexion and constrained internal rotation. A lower limb length discrepancy is present due to local growth aggravation at the left hip, currently patient using shoe with lift modifications on her left leg. In any case, there has been no complaint of pain, swollen or seropurulent releases throughout the last 18 months